The unified modeling language model of an object oriented debugger system. - Mohd Ariffin, Noor Afiza; Mohd Sani, Nor Fazlida; Atan, Rodziah (Springer Berlin Heidelberg, 2013)
In this paper will explain a model that being used to develop an Object Oriented Debugger (OOD). Unified Modeling Language (UML) is the best choice model and suitable to design the Object Oriented Debugger which will be developed in an object oriented programming environment. The model will provide an ability to capture the characteristics of a system by using notations in the process of designing and implementing the system. The objective of this paper is to capture the structure and behavior of the Object Oriented Debugger system by using the UML diagram. The model also can ease the readability of the documentation for the maintenance purposes. This paper starts with explanation about the concepts of Object Oriented Debugger and has divided into three sections which include creating use case, capturing process flow and finding objects interactions. Appropriate UML diagrams for Object Oriented Debugger system are presented in relevant sections of this paper.